Tayside TB Pathway: A Quality Improvement Project. Issue 2 (28th February 2020) - Wilson, Aline; Jordan, Rose
Abstract : Aims: The aim of this project was to look at our local practice of identifying and managing patients with mycobacterium tuberculosis (MTB) and non pulmonary NTM. In Tayside, the care of patients with MTB is shared between the Infectious Diseases physicians and the Respiratory physicians. We aim to improve communication and identify any issues with continuity of care and create solutions to standardise the care our patients receive. Methods: We performed an initial audit of patients that were currently receiving or had recently completed treatment for MTB and non pulmonary NTM. We collected data from 26 patients between January 2017 - July 2018. Results: Some of the results are as follows: Out of the 26 patients, only 14 (53.8%) of those had a documented start date of treatment on the initial clinic letter. 92.3% had a documented treatment regime on clinic letter. 88.4% (23 out of 26 patients) had a documented diagnosis (specifying site) on clinic letter. Only 46% had a complete BBV screen, 35% had an incomplete BBV screen and 19% had none. Outcome: After performing the initial audit and assessing the areas of improvement, we were able to create our "Tayside TB Pathway". The idea behind this was to create a more cohesive and streamlined approach to TB care whilst involving all members of the MDT. The pathway was created to be straightforward and allow us to have a "centralised hub" to oversee the important steps involved in the management and prompt these to be performed where needed.